THE IMPROVEMENT OF ANSWERING QUESTIONS SKILLS IN SOLUBILITY AND SOLUBILITY PRODUCT CONCEPT BY PROBLEM SOLVING LEARNING MODEL - ria marthandila; noor fadiawati; chansyanah diawati (Universitas Lampung, 2012)
The aim of this research is to describe the effectiveness of problem solving learning model in solubility and solubility product concept to enhance skill in answering questions. Students who became the subject of this research was XI grade of Science 1 Batanghari Senior High School in Batanghari Academic Year 2011/2012. This research used the pre-experimental method and one group pretest-posttest design. The effectiveness of problem solving learning model was determined based on the average value of n-Gain. The results of this research showed that the average value of n-Gain of skills in answering questions about definition and why were 0,7 and 0,33. Thus, it can be concluded that the problem solving learning model in solubility and solubility product concept effective to enhance answering question about definition was in high category and answering whyquestion was in medium category.Keywords: problem solving learning, answering questions skills.